"COVID Toes" in Three Siblings. Issue 12 (20th July 2021) - Feder, Henry M.
Abstract : Dermatologists reported an outbreak of pernio (red to purple swollen painful toes) during the COVID-19 pandemic. Most subjects lacked positive CoV-19 polymerase chain reaction (PCR) or antibodies or a preceding illness. The dermatologists termed the illness "COVID toes." Pernio usually affects adults versus "COVID toes" usually children. Pernio is preceded by a clear history of exposure to wet and cold. Patients with "COVID toes" lack this history. Also, it is not unusual for multiple family members to have "COVID toes." Our case report describes "COVID toes" in an 18-year-old with no preceding illness, a negative SARS-CoV-19 PCR, and an initially negative SARS-CoV-19 antibody, and also his 2 siblings also developed "COVID toes." In our index case, repeat SARS-CoV-19 antibodies were positive. Seroconversion has rarely been reported in patients with "COVID toes." Why most "COVID toes" patients lack a clinical history of COVID-19 and are SARS-CoV-19 PCR and antibody negative is a mystery.